Mechanisms and grading of nocturia: Results from a multicentre prospective study. Issue 3 (13th October 2020) - Bozkurt, Ozan; Irer, Bora; Kizilay, Fuat; Erbatu, Oguzcan; Sen, Volkan; Cinar, Onder; Ongun, Sakir; Cihan, Ahmet; Ozdemir, Turan; Tasdemir, Dogu; Ucer, Oktay; ,
Abstract: Objective: To identify the pathophysiological mechanisms of nocturia and the correlation of these mechanisms with nocturia severity. Methodology: After approval by the local ethics committee, all patients with nocturia (≥1 nocturnal void/night) were included and filled the Overactive Bladder questionnaire, Nocturia Quality of Life, Incontinence Questionnaire ‐ Male Lower Urinary Tract Symptoms (male), International Consultation on Incontinence Questionnaire ‐ Female Lower Urinary Tract Symptoms (female) and 3‐day frequency‐volume chart. Patients were divided into three groups according to the severity of nocturia: group 1 consisted of patients with mild (1‐2 voids/night), group 2 with moderate (3‐4 voids/night) and group 3 with severe nocturia (>4 voids/night). Comparative analysis was performed between groups, and P < .05 was deemed as statistically significant. Results: About 68.1%, 64.1% and 8.7% of the patients had nocturnal polyuria (NP), reduced bladder capacity and global polyuria, respectively. 42.7% of the patients had mixed nocturia. 6.1% of the patients did not comply with the aforementioned subtypes and defined as isolated nocturia. Regarding the severity of nocturia, 155 (41%) patients had mild, 167 (45%) patients had moderate and 57 (15%) patients had severe nocturia. Increased nocturia severity was related with decreased quality of life; higher age, urinary tract symptom scores, nocturnal urine volume, evening fluid consumption and beta‐blocker medication rates. Increased nocturia severity was also associated with higher NP, global polyuria and reduced bladder capacity rates. Conclusions: Nocturia mechanisms may vary between mild and moderate to severe nocturia groups according to the present study. Nocturia grading with identification of subtypes may help for better standardisation of the diagnostic and treatment approaches as well as for the design of future clinical trials.